Hate speech on the rise: lacunae in Malaysian law - Wan Mohd Nor, Murni (CLJ Legal Network, 2016)
Malaysia is made up of many racial and religious groups whose fundamental rights have been protected by and enshrined in the Federal Constitution. However, our history has witnessed the unfortunate events of racial riots and at present, tensions still exist beneath the surface. The use of hate speech in our multicultural country has increased with the advent of social media. This has resulted in hateful and violent acts being committed which threaten peace and harmony in the country, causing the Government to consider the promulgation of a specific legislation for the regulation of hate speech. This paper firstly looks at governmental efforts that were made to strengthen racial harmony. Then, the author discusses the recent instances of racial and religious animosity that has been aggravated by social media which has brought about tensions affecting the community. The paper also highlights the lacunae in Malaysian law in addressing issues arising from hate speech. Finally, the author concludes by discussing the necessity of having a specific legislation for hate speech in order to adequately address the magnitude of problems that will ensue as a result of the law's failure in safeguarding the people from its harm.